2005
DOI: 10.1186/1471-2334-5-110
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial isolates from blood cultures of children with suspected septicaemia in Calabar, Nigeria

Abstract: BackgroundSepticaemia is a common cause of morbidity and mortality among children in the developing world. This pattern has changed little in the past decade. Physical signs and symptoms, though useful in identifying possible cases have limited specificity. Definitive diagnosis is by bacteriologic culture of blood samples to identify organisms and establish antibiotic susceptibility. These results are usually not available promptly. Therefore a knowledge of epidemiologic and antimicribial susceptibility patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
96
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 6 publications
25
96
10
Order By: Relevance
“…This observation is in accordance with the study conducted by Karki et al 6 in Nepal, Karthikeyan et al 13 in India, Meremikwu et al 14 in Nigeria and Aziz et al 15 in Pakistan.…”
Section: Discussionsupporting
confidence: 81%
“…This observation is in accordance with the study conducted by Karki et al 6 in Nepal, Karthikeyan et al 13 in India, Meremikwu et al 14 in Nigeria and Aziz et al 15 in Pakistan.…”
Section: Discussionsupporting
confidence: 81%
“…While in some studies it has been reported as high as 44.7% (Ethiopia) (12) and 45.9% (Nigeria) (13), in other studies it is about 20% (14). It was 11.9% in this study, which can be explained by the different clinical criteria for suspicion of sepsis and taking blood samples, the technique of culture (traditional culture vs. BACTEC), quality of life and measures of health care and hospital services in various countries (15,16).…”
Section: Bloodmentioning
confidence: 96%
“…The isolation rate of bacteria in this study is comparable to rates reported in Nigeria (45.9%), India (52.6%), Pakistan (54.0%) and Uganda (37.5%). 34,33,39,40 Lower isolation rates were reported in Ethiopia (23.1%-27.9%) and studies conducted in other developing countries e.g. in Iran (6.6%) (28), Bahrain (4.2%).…”
Section: Discussionmentioning
confidence: 99%
“…28 Clinical assessment by using signs and symptoms is a useful guide to provisional diagnosis of neonatal sepsis. 34 Reports from India showed that 50-60% of septic babies were premature neonates and verylow-birth-weight (VLBW) were more vulnerable. In our cases, 48.0% were low-birth-weight (LBW) babies and 20.8% were premature neonates.…”
Section: Discussionmentioning
confidence: 99%